Schistosoma japonicum cathepsin B2 (SjCB2) facilitates parasite invasion through the skin - Zhu, Bingkuan (PLoS Negl Trop Dis, 2020)
Cercariae invasion of the human skin is the first step in schistosome infection. Proteases play key roles in this process. However, little is known about the related hydrolytic enzymes in Schistosoma japonicum. Here, we investigated the biochemical features, tissue distribution and biological roles of a cathepsin B cysteine protease, SjCB2, in the invasion process of S. japonicum cercariae. Enzyme activity analysis revealed that recombinant SjCB2 is a typical cysteine protease with optimum temperature and pH for activity at 37°C and 4.0, respectively, and can be totally inhibited by the cysteine protease inhibitor E-64. Immunoblotting showed that both the zymogen (50 kDa) and mature enzyme (30.5 kDa) forms of SjCB2 are expressed in the cercariae. It was observed that SjCB2 localized predominantly in the acetabular glands and their ducts of cercariae, suggesting that the protease could be released during the invasion process. The protease degraded collagen, elastin, keratin, fibronectin, immunoglobulin (A, G and M) and complement C3, protein components of the dermis and immune system. In addition, proteomic analysis demonstrated that SjCB2 can degrade the human epidermis. Furthermore, it was showed that anti-rSjCB2 IgG significantly reduced (22.94%) the ability of the cercariae to invade the skin. The cysteine protease, SjCB2, located in the acetabular glands and their ducts of S. japonicum cercariae. We propose that SjCB2 facilitates skin invasion by degrading the major proteins of the epidermis and dermis. However, this cysteine protease may play additional roles in host-parasite interaction by degrading immunoglobins and complement protein.